2018
DOI: 10.1021/acs.jpcc.8b05272
|View full text |Cite
|
Sign up to set email alerts
|

Strain-Enhanced Li Storage and Diffusion on the Graphyne as the Anode Material in the Li-Ion Battery

Abstract: The density functional theory is used to study the effect of the external biaxial strain on the adsorption and diffusion of Li on the graphyne as an anode material in the Li-ion battery (LIB). The increasing adsorption energy of Li on graphyne appears with the larger external biaxial strain. The Li capacity of the Li6C6 configuration for graphyne reaches 2233 mA h/g under the 12% strain, which is six times that of graphite (372 mA h/g) and two times that of graphyne without strain (1117 mA h/g). The average op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(31 citation statements)
references
References 79 publications
3
27
0
Order By: Relevance
“…γ‐Graphyne ( n = 1) has been theoretically calculated to be the candidate of graphene as next‐generation lithium‐ion battery anode . Mohajeri et al argued that γ‐graphyne shows improved Li + storage mechanism by hosting Li + both between the carbon sheets and in the big conjugate rings, indicating higher capacity than that in all sp 2 ‐hybridized carbon materials like graphite .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…γ‐Graphyne ( n = 1) has been theoretically calculated to be the candidate of graphene as next‐generation lithium‐ion battery anode . Mohajeri et al argued that γ‐graphyne shows improved Li + storage mechanism by hosting Li + both between the carbon sheets and in the big conjugate rings, indicating higher capacity than that in all sp 2 ‐hybridized carbon materials like graphite .…”
Section: Introductionmentioning
confidence: 99%
“…Lee and co‐workers have found that C 6 Li 3 composite of Li‐intercalated multilayer γ‐graphyne manifested an ultrahigh capacity of about 1000 mAh g −1 . Very recently, Zhang et al studied the strain‐enhanced Li + storage and diffusion on γ‐graphyne as the anode in LIBs by using the density functional theory . It has been found that the maximum Li + capacity of the multilayer graphyne under 12% strain can reach 2233 mAh g −1 , which is two times that of γ‐graphyne without strain (1117 mAh g −1 ).…”
Section: Introductionmentioning
confidence: 99%
“…The simulated results indicate that the Li ions can diffuse through both in-plane and out-of-plane pathways with a proper diffusion barrier in bulk GDY [48] . Compared to in-plane diffusion, quite lower barriers are estimated while the lithium diffuses in the out-of-plane direction [49] . This can be understood from the fact that the uniform distribution of nanopores provides extra diffusion channels for lithium ions in the perpendicular direction to the two-dimensional(2D) GDY carbon plane [50] .…”
Section: Introductionmentioning
confidence: 97%
“…[16][17][18] Compared with the graphene composed merely carbon hexagons, the asymmetrically conjugated p electrons and located large pores endow the GYs with a more promising prospect in LIBs. [19][20][21][22][23][24] Recently, a new member of the GYs family, the porous hydrogen substituted GY (HsGY) nanosheets was synthesized using the facile bottom-up synthetic approach. 25 The experiments showed that the exible HsGY lms as the anode in lithium and sodium ion batteries exhibited excellent electrochemical properties.…”
Section: Introductionmentioning
confidence: 99%